2020
DOI: 10.4046/trd.2020.0045
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bedside Ultrasonography in Assessment of Diaphragm Function as a Predictor of Success of Weaning in Mechanically Ventilated Patients

Abstract: Background: Weaning failure is common in mechanically ventilated patients, and if ultrasound can predict weaning outcome remains controversial. The purpose of this study was to evaluate the diaphragmatic function (thickness and excursion) measured by ultrasound as a predictor of the extubation outcome. Methods: We included 62 mechanically ventilated patients from the chest intensive care unit in this study. Sixty-two patients who successfully passed the spontaneous breathing trial (SBT) were enrolled. The tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In the present study, LMWH inhibited oxidative stress, inflammation, and apoptosis and increased antioxidant activity, eventually leading to recovery from pathological impairment through repressing HIF-1α. Furthermore, LMWH improved the contractile excursion and thickening fraction of damaged diaphragms; these parameters are commonly employed in the evaluation of diaphragm dysfunction in clinical practice [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, LMWH inhibited oxidative stress, inflammation, and apoptosis and increased antioxidant activity, eventually leading to recovery from pathological impairment through repressing HIF-1α. Furthermore, LMWH improved the contractile excursion and thickening fraction of damaged diaphragms; these parameters are commonly employed in the evaluation of diaphragm dysfunction in clinical practice [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding can be explained by prolonged MV evoking significant declines in both passive and active diaphragm contractile force by increasing proteolysis and reducing the generation of myofibrillar proteins [ 61 ]. Mounting studies describing the application of bedside ultrasonography assessment of the diaphragm in the process of discontinuing ventilator use suggest that both methods of measuring the thickening fraction of diaphragm muscles and excursion are reliable predictors of ventilator liberation and extubation outcomes [ 9 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Negligible to moderate correlations with spirometry (32,77), respiratory distress (20,32,33,39) Negligible correlation with MV duration, dynamic compliance (53) and ICU length of stay (39) Negligible correlation with ventilator-derived diaphragmatic measures (32) or muscle strength…”
Section: Diaphragm Thickening Fractionmentioning
confidence: 99%
“…Negligible to low correlations with spirometry (32, 62), cough peak flow (31), respiratory distress (32,33), dynamic lung compliance (53) and magnetic stimulated diaphragmatic measures (56) High correlation with ventilator-derived diaphragmatic measures (32) Low to moderate correlations with diaphragm thickening fraction (61,63) Low correlation with severity of illness and MV duration (53) Moderate correlation between left and right measurements (49)…”
Section: Diaphragm Excursionmentioning
confidence: 99%
“…However, another study showed that LUS before SBT failed to predict SBT failure [ 31 ] which highlights the fact that not one method should be used in isolation to make decisions regarding critically ill patients. Although out of scope of this review, ultrasound of the heart, diaphragm and pleura may also be useful in detecting obstacles to successful extubation [ 32 , 33 ].…”
Section: Weaning From Mechanical Ventilationmentioning
confidence: 99%